Gender, security, and the environment: lessons from the Ganges-Brahmaputra-Meghna water basin - Detraz, Nicole, author; Betsill, Michele, advisor (Colorado State University. Libraries, 2009)
Environmental security has come to represent a way for scholars and policymakers to link the concepts of traditional security scholarship to the environment. Within academia, scholars use the concept of environmental security in several different ways, as well as using alternative terms to convey a relationship between security and the environment. While there has been some scholarly work conducted that seeks to identify the ways that academics link these concepts, there has been little systematic work done that examines the intersection between approaches to environmental security and gender. This dissertation argues the necessity of including gender into the discourses on security and the environment. In the project I address the theoretical and practical implications of ignoring the gendered aspects of security and the environment and the possibilities for introducing gender into theoretical and political debates linking environment and security. The key questions that this project explores are (1) How are the issues of security and the environment linked in theory and practice; (2) To what extent is gender a part of these discussions; and (3) What are the implications of how these issues are linked? I undertook three research steps for the dissertation. Step 1-discourse analysis of the academic literature linking environment and security. This step involved examining the academic literature using discourse analysis to identify three distinct discourses linking environment and security. Step 2-gender analysis of the three major discourses linking environment and security. This step consisted of tracing the presence and absence of gender in the security and environment debates in order to understand the place of gender currently, and the possible inclusion of gender into the discourses. Step 3-case studies of water issues in South Asia. These case studies explore some of these ideas in the context of real world policy discussion to see whether these same discourses inform policy debates; whether and how gender is considered in these policy debates; and refine some of the ideas/concepts about how gender matters and could be incorporated in the academic discussions.
Keywords: environmental security; Ganges-Brahmaputra-Meghna; gender; secruity studies; international law; gender; national security; water; river basins